Change of spinal range of motion, lungs volume and pain evaluation inpatients with ischemic heart disease after bypass surgery - Bolach Eugeniusz; Bolach Bartosz; Rachwalik Wojciech; Bialic Malgorzata (Kharkov National Pedagogical University, 2012)
The purpose of this study is to evaluate the changes in range of motion in the joints of the spine in the sagittal plane, motion of the chest, lung vital capacity, minute respiratory rate as well as evaluation of pain intensity in men after cardiac surgery. The study was to evaluate changes in range of motion in the joints of the spine in the sagittal plane, motion of the chest, lung vital capacity, the number of breaths per minute and the evaluation of pain intensity in 25 men with coronary artery disease before and after surgery heart bypass. Subjects were men aged from 56 to 71 years, with an average age of 61. The study included measurements of joint mobility of the spine, chest, lung vital capacity and respiratory rate per minute and the measurement of pain intensity. In male subjects were also interviewed, including: personal information (initials), age, education, type of work undertaken by him, and motor activity.